Raising the bar in ulcerative colitis management - Fabrizio Fanizzi; Mariangela Allocca; Gionata Fiorino; Alessandra Zilli; Federica Furfaro; Tommaso Lorenzo Parigi; Laurent Peyrin-Biroulet; Silvio Danese; Ferdinando D’Amico (Therapeutic Advances in Gastroenterology)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease characterized by growing incidence and prevalence around the world in the last few decades. The range of available existing treatment and strategies for its management is being implemented. Given the introduction of newly developed molecules and the lack of specific guidelines, drug positioning may represent a tough clinical challenge. UC management is mostly medical, and it has been shifting toward a more personalized approach with the aim to create a tailored strategy depending on the patient’s profile. A treat-to target strategy seems to be the best approach to reach disease control as it allows to carry out therapeutic choices based on objective and specific parameters: histological, ultrasonographic, and molecular targets may add to the already used clinical, endoscopic, and biochemical targets. In addition, dual-targeted therapy has emerged as an attractive therapeutic strategy for patients not achieving remission. This review aims to provide an overview of the available strategies to raise the bar in UC.